MEASURING ORAL PRESENTATION ABILITY OF ENGLISH STUDY PROGRAM STUDENTS - Hisanah, Aliyah; Daud, Afrianto; Purwanti, Indah Tri (Universitas PGRI Sumatera Barat, 2024)
This study aims to find out the ability of students in conducting oral presentations. An oral presentation is one of the skills in speaking. This research is descriptive quantitative and has only one variable, namely the students' oral presentation ability. The population of this study was taken from second-year students of one of the English study programs in Riau with a sample total of 34 students. Based on the results of the analysis, the researcher concluded that the average ability of second-year students of one of the English study programs in Riau in 2022/2023 has a good ability to do oral presentations. The results of the analysis showed that 18% of 34 students had very good presentation ability, 76% of 34 students had good presentation ability, and 6% of 34 students had fair presentation ability on average, and no students were in the poor category. The conclusion is that the oral presentation ability of students in the second year of one of the English study programs in Riau is in the good category.